Utility of a guiding catheter for conduction system pacing: An early multicenter experience - De Pooter, Jan; Bulava, Alan; Gras, Daniel; Timmer, Stefan; Chin-Pang Chan, Gary; Clementy, Nicolas; Pathak, Rajeev K; Healy, Stewart; Lüsebrink, Ulrich; Zanon, Francesco (Heart rhythm O2, 2024)
BACKGROUND: Conduction system pacing (CSP), either as His bundle pacing (HBP) or as left bundle branch area pacing (LBBAP), may be superior to right ventricular apical or septal pacing. OBJECTIVE: The study sought to present acute results for a new guiding catheter (Biotronik Selectra 3D) designed for CSP implantations of a retractable screw-in lead (Biotronik Solia S). METHODS: The primary endpoint of the prospective, international nonrandomized BIO|MASTER.Selectra 3D study was freedom from catheter-related serious adverse device effects (SADEs) within 1 week of lead implantation. RESULTS: Of 157 enrolled patients, CSP was achieved in 147 (93.6%) patients. No SADEs occurred within 7 days. LBBAP was achieved in 82 patients (45 as crossover from an HBP attempt) and HBP in 65 (44.2%) patients. In centers considering both HBP and LBBAP, the CSP implantation success approached 99%. Successful CSP implantations lasted on average ∼50 minutes (fluoroscopy ∼6 minutes). Most procedures (87.9%) needed only 1 catheter, even after switch from HBP to LBBAP. The catheter's handling was rated largely positive. In patients without bundle branch block, mean QRS duration increased from 106 ms (intrinsic) to 122 ms (CSP) (P = .001). In patients with bundle branch block, mean QRS duration decreased from 151 ms (intrinsic) to 137 ms (CSP) (P = .004). CONCLUSION: The Selectra 3D catheter is a valuable tool for HBP and LBBAP implantations of the stylet-supported pacemaker leads. When implanters considered both HBP and LBBAP, the success rate was ∼99%. Flexibility to change between different approaches may be advisable in heterogeneous and challenging areas, such as CSP implantations.